PENGARUH PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR TEMATIK PESERTA DIDIK KELAS IV SEKOLAH DASAR BAWAMAI - Diah May Lestari; Marzuki Marzuki; Kartono Kartono (Universitas Tanjungpura, 2019)
Abstract.This study aimed to analyze how much influence the Scientific Approach has on the Learning Outcomes of Students on Class IV Thematic Learning in Pontianak Bawamai Elementary School. Using the experimental method with the form of research that is pre-experimental design with the experimental design of one group pretest-posttest design. Using a sample of the population because there is only one class, class IV, which amounts to 40. Research instrument used to measure student learning outcomes in the form of knowledge tests. The data collection technique in this study was a measurement technique. The research obtained an average experimental class pretest was 76.58 and the post-test average of the experimental class was 83.70. Hypothesis test results using t-test obtained t_count = 6.104 for dk = 39 and α = 5% obtained t_table = 2.023, which means t_count (6.104)>t_table (2.023), then Ha thus accepted. So, it can be concluded that there were differences in student learning outcomes at the pretest and posttest. From the results of the calculation of the effect size (ES) of 0.97 (high). Thus the process approach to thematic learning has a high influence on the learning outcomes of Grade IV students at Pontianak Bawamai Elementary School.Keywords: Contextual Learning, Influence, Poetry.